2011
DOI: 10.1155/2011/845025
|View full text |Cite
|
Sign up to set email alerts
|

Straightening Regulation Optimization on the Residual Stress Induced by the Compound Roll Straightening in the Heavy Rail

Abstract: Residual stress is very important to the straightened quality of rail, this paper adopts explicit dynamics FEM to study on residual stress. We established compound roller model and calculated the residual value of heavy rail through 9 roller horizontal straightening and 8 roller vertical straightening. The reductions of straightening rollers are taken as the main effective factor to the residual stress in the straightening process. We adopt orthogonal calculation method to obtain the main effective factor to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…For a given distance between the rollers, there are many sets of setting values which result in a straight rail. With appropriately optimized settings, it is possible to reduce the level of residual stresses in the rails, which has been confirmed both by numerical simulations and tests in industrial conditions [10][11][12][13][14][15][16][17][18]. literature analysis did not reveal any publications devoted to the research on changing the pass design of straightener rolls to the residual stress level.…”
Section: Introductionmentioning
confidence: 84%
“…For a given distance between the rollers, there are many sets of setting values which result in a straight rail. With appropriately optimized settings, it is possible to reduce the level of residual stresses in the rails, which has been confirmed both by numerical simulations and tests in industrial conditions [10][11][12][13][14][15][16][17][18]. literature analysis did not reveal any publications devoted to the research on changing the pass design of straightener rolls to the residual stress level.…”
Section: Introductionmentioning
confidence: 84%
“…in the work [7] it was demonstrated that one of the reasons for the appearance damage and cracks in railway rails accelerating development of typical rail head defects are residual stresses. in turn, in paper [8] adopts explicit dynamics FEM to study on residual stresses where the optimal regulation was obtained, in which the residual stresses are the smallest. The study [9] was also devoted to clarify the residual stress distribution by simulation with a fully three-dimensional model taking into account both the bending and contact process.…”
Section: Introductionmentioning
confidence: 99%
“…Biempica et al 6 reduced the residual stress by improving finite element model with contact conditions between the rails, the rollers, and the kinematic hardening material model. Finite element and orthogonal calculation 7 can also reduce the residual stress of straightened rails. Pernı´a et al 8 combined finite element method and genetic algorithm to determine the best roller position to ensure the minimum residual stress following roller straightening.…”
Section: Introductionmentioning
confidence: 99%